Variation in countermovement jump metrics following competitive soccer matches throughout a season in professional players - Mohr, P.; Bishop, C.; Pupo, J. (Sport Sciences for Health, 2025)
Purpose This study aimed to analyze the variations in the countermovement jump (CMJ)-derived metrics in professional soccer players due to match exposure; in addition, it was analyzed if these responses are dependent on the time played by the athlete.